The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1037/0735-7028.28.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Dual-relationship dilemmas of rural and small-community psychologists.

Abstract: Sixteen licensed psychologists who lived and practiced in rural areas and small communities participated in interviews about ethical dilemmas they faced in daily practice. Dilemmas involving professional boundaries were identified as significant concerns for all of the psychologists. Major themes were the reality of overlapping social relationships, the reality of overlapping business relationships, the effects of overlapping relationships on members of the psychologist's own family, and the dilemmas of workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(127 citation statements)
references
References 14 publications
0
126
0
1
Order By: Relevance
“…The need for sensitivity to boundary and dual-relationship issues by therapists who are members of small communities they serve, a concern many therapists discussed, is a recognized issue in psychotherapy practice (Brown, 1991;Morrow, 1999;Schank & Skovholt, 1997). Because BDSM activities involve sexuality and power, it is not surprising that transference and countertransference reactions involving these themes might emerge during therapy.…”
Section: Discussionmentioning
confidence: 93%
“…The need for sensitivity to boundary and dual-relationship issues by therapists who are members of small communities they serve, a concern many therapists discussed, is a recognized issue in psychotherapy practice (Brown, 1991;Morrow, 1999;Schank & Skovholt, 1997). Because BDSM activities involve sexuality and power, it is not surprising that transference and countertransference reactions involving these themes might emerge during therapy.…”
Section: Discussionmentioning
confidence: 93%
“…Probably the most frequent ethical dilemma raised by psychologists working in rural communities involves the issue of multiple relationships with clients (Barbaopulos & Clark, 2003;Brownlee, 1996;Erickson, 2001;Gates & Speare, 1990;Green & Mason, 2002;Hargrove, 1986;Jennings, 1992;Judd et al, 2002;Roberts et al, 1999;198 ALLOTT & LLOYD Schank, 1998;Schank & Skovholt, 1997;Simon & Williams, 1999). Indeed, Helbok et al (2006) found that rural psychologists encountered multiple relationships significantly more often than urban psychologists.…”
Section: Multiple Relationshipsmentioning
confidence: 94%
“…The fact that the majority of literature relating to professional boundaries is also, 'terse, rigid, pathologising [and based on] fear tactics' (Cleret, 2005, p48) means that therapists are often extremely hesitant to have discussions with either their colleagues or supervisors about any dilemmas they might have with regard to maintaining their boundaries (Clark 2009b;Schank & Skovholt, 1997). In instances of client death, this hesitancy and fear is likely to be heightened, since whilst rules and codes currently exist in relation to what constitutes 'appropriate' professional conduct in relation to boundaries within the therapeutic relationship, there is a void in the literature about what constitutes appropriate therapeutic conduct after a client has died.…”
Section: Professional Boundaries: the Interplay Between The Personal mentioning
confidence: 98%
“…Furthermore, since the breaching of professional boundaries remains such a controversial and taboo subject within therapy (Cleret, 2005); and engaging in such breaches can be 'professionally ruinous' (Glass, 2003, p429); therapists are left having to second-guess about the ethics of their behaviours and interventions (Schank & Skovholt, 1997).…”
Section: Professional Boundaries: the Interplay Between The Personal mentioning
confidence: 99%